Can we expect re-emergence of infectious diseases in the near future? - Jacek Pruszyński; Dorota Cianciara; Justyna Grudziąż-Sękowska; Inga Włodarczyk-Pruszyńska; Bartosz Kobuszewski; Wojciech Zgliczyński; Irena Pruszyńska (Kazimierz Wielki University, 2022)
Ever since Hippocrates expressed the view that environmental factors can influence disease incidence, attempts have been made to link the emergence of disease, especially outbreaks of infectious diseases, with the various factors that contribute to their occurrence. Among the possible causes favoring the spread of pathogens and the increase in the incidence of infectious diseases, environmental and social conditions are mentioned. An unprecedented set of new conditions has made the human population more vulnerable and more susceptible to infectious diseases than ever before. It is possible that the observed contemporary patterns of development and spread of infectious diseases may be seen as heralds of a new stage of epidemiological transformation characterized by an increased risk of infectious disease epidemics. In past centuries, one of the hallmarks of infectious disease plagues has been their unpredictability. Currently, warning forecasts prepared by scientists do not always translate into preventive measures.